Zein Nanoplatforms for Functional Promotion of Pro-apoptosis and Antiproliferation Induced in Human Breast Carcinoma MCF7 Cells by Pterostilbene - Al-Sawahli, Majid Mohammad; Zarka, Mohamed A.; Ghareeb, Mowafaq Mohammed; Kutbi, Hussam Ibrahim; Kammoun, Ahmed Kamal; Noreddin, Ayman M.; El-Telbany, Dalia Farag A. (Perspective of Recent Advances in Medical Research Vol. 12, 2023)
The aim of current study was to investigate potential of PTS-ZN NSs formulation on ameliorating cytotoxicity, pro-apoptotic and oxidative stress potentials of PTS in MCF-7 cells. PTS-ZN NSs were synthesised using the liquid-liquid phase separation method. The formulations developed were evaluated in terms of particle size analysis, encapsulation efficiency, and in vitro diffusion. Cytotoxicity, uptake, cell cycle progression, Annexin-V assay, apoptotic genes mRNA expression, and biochemical assays were also performed. Five formulations of PTS-ZN NSs (P1-P5) were prepared according to liquid–liquid phase separation method to diminish the use of solvents. The study indicated that apoptosis in MCF-7 cells was confirmed and augmented through caspases dependent signaling pathways and inhibition of CDK1 activity due to use of ZN-NSs in delivery of PTS in comparison with free PTS. Promising research outcomes included high EE% nanocomposites, 36 h extended PTS diffusion, a synergized cytotoxicity profile, enhanced MCF-7 cells uptake, ameliorated apoptosis induced potential, enhanced mRNA expression of CASP3, CASP7 and CDK1 genes and significant oxidative stress.